The ESCRT-III Protein Chmp1 Regulates Lipid Storage in the Drosophila Fat Body - Austin M. Fruin; Kelly E. Leon; Justin R. DiAngelo (Medical Sciences, 2022)
Defects in how excess nutrients are stored as triglycerides can result in several diseases including obesity, heart disease, and diabetes. Understanding the genes responsible for normal lipid homeostasis will help understand the pathogenesis of these diseases. RNAi screens performed in Drosophila cells identified genes involved in vesicle formation and protein sorting as important for the formation of lipid droplets; however, all of the vesicular trafficking proteins that regulate lipid storage are unknown. Here, we characterize the function of the Drosophila Charged multivesicular protein 1 (Chmp1) gene in regulating fat storage. Chmp1 is a member of the ESCRT-III complex that targets membrane localized signaling receptors to intralumenal vesicles in the multivesicular body of the endosome and then ultimately to the lysosome for degradation. When Chmp1 levels are decreased specifically in the fly fat body, triglyceride accumulates while fat-body-specific Chmp1 overexpression decreases triglycerides. Chmp1 controls triglyceride storage by regulating the number and size of fat body cells produced and not by altering food consumption or lipid metabolic enzyme gene expression. Together, these data uncover a novel function for Chmp1 in controlling lipid storage in Drosophila and supports the role of the endomembrane system in regulating metabolic homeostasis.